Acoustic radiation force impulse elastography of the eyes of brachycephalic dogs - Abreu, T. G. M. [UNESP]; Feliciano, M. A. R. [UNESP]; Renzo, R. [UNESP]; Kobashigawa, K. K. [UNESP]; Chacaltana, F. D. Y. C. [UNESP]; Crivelaro, R. M. [UNESP]; Silveira, C. P. B. [UNESP]; Cruz, N. R. N. [UNESP]; Aldrovani, M. [UNESP]; Maronezi, M. C. [UNESP]; Silva, P. A. [UNESP]; Thiesen, R.; et al. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
Eyes from brachycephalic dogs were studied by acoustic radiation force impulse (ARFI) elastography to establish quantitative and qualitative reference values related to the shape and rigidity of some ocular structures. Eighty-four eyes from 42 adult brachycephalic dogs were included in this study. Animals were subjected to physical, laboratory, and ophthalmic examinations. Following confirmation of good health, the dogs were subjected to ultrasonography and ARFI elastography, emphasizing the optic nerve, ciliary body, and lens. On qualitative elastography, homogeneous characteristics were observed on the ciliary body and optic nerve. Aqueous and vitreous humors were visualized as mosaic-like images. Quantitative elastography showed the mean optic nerve shear wave velocity (SWV) was 1.01 +/- 0.27m/s, temporal ciliary body was 0.91 +/- 0.24m/s, and nasal ciliary body was 0.91 +/- 0.3m/s. The SWV of the lens values were out of range, this value was not detectable by this software. Elastography has proved to be a non-invasive procedure and feasible in dogs. The establishmentof the parameters of degree of rigidity of ocular structures will serve as a baseline for animals with eye disorders. Results may be extrapolated to primary research on the applicability of ARFI in the evaluation of ocular bulb in humans.
Keywords: canine; ocular structures; ultrasound